From university student to program director - Vinkóczi, Tamás; Hamuth, Mónika (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
As a student of Management and Organization at Széchenyi István University, I first heard about the Kautz Gyula College of Economics, which I found interesting in terms of professional development and networking. In my second year of studies, I decided to apply to the college, which was also the date of my admission, so I became a member of the college from the 2014/2015 academic year. In cooperation with the university and the Gyula Kautz Faculty of Economics, the student organization had already organized numerous lectures on finance, economics, and management lectures were already being organized by the student organization, and attending them was an integral part of being a member. The program director of the college at the time—who later became my doctoral advisor—was Gábor Kovács, who did his job with great enthusiasm. Even in this early stage of my membership in the college, I was able to participate in the organization of one of our biggest events, the National Financial Case Study Competition, gaining experience in event management and having the opportunity to meet students from other universities. During my studies, I participated in several economics competitions. As my interests lay in simulation competitions, my fellow college students and I participated in the Student Management Championship several times and even made it to the finals.